Synonymy of the genus Arisocerus Brennan, 1970 with the genus Herpetacarus Vercammen-Grandjean, 1960 (Trombidiformes: Trombiculidae) - Jacinavicius, Fernando De Castro; Bassini-Silva, Ricardo; Welbourn, Cal; Ochoa, Ronald; Barros-Battesti, Darci Moraes [UNESP] (Systematic & Applied Acarology Soc London, Natural History Museum, 2019)
The genus Arisocerus is synonymized with Herpetacarus. Redescriptions of Herpetacarus amapensis comb. nov. and Herpetacarus hertigi comb. nov., are provide with new Brazilian locality and host records for H. hertigi comb. nov.
Keywords: Mammals; ectoparasite; chiggers; Brazil